2017
DOI: 10.3892/ol.2017.6167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of primary tumor location and tumor size on the response to radiotherapy for liver metastases from colorectal cancer

Abstract: Abstract. Metastatic liver tumors (MLTs) from colorectal cancer (CRC) are often treated with stereotactic body radiation therapy (SBRT). The present study aimed to examine the predictive factors for response of MLTs to SBRT. A total of 39 MLTs from 24 patients with CRC were retrospectively analyzed. Radiotherapy for MLT was typically performed with a prescribed dose equivalent to a biologically effective dose (BED) 10 of 100 Gy. The median follow-up period was 16 months (range, 5-64 months). The median prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
1
13
0
2
Order By: Relevance
“…Various parameters are collected for each colorectal cancer patient such as gender, age, body mass index (BMI), family history (FH), smoking habit, alcohol consumption, and pathological finding including the tumor size, tumor differentiation, circumferential involvement, tumor stage, node stage etc. Several studies considered the tumor size as an important factor for determining the stage of colon cancer [6][7][8][9], whereas some studies focused on evaluating the tumor size as a prognostic factor for the colorectal cancer prognosis [10,11]. It has also been found that the tumor size is not only an essential factor in determining the TNM stage of the colon cancer; it is also a significant predictor, which can be used for estimating the survival period of the patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Various parameters are collected for each colorectal cancer patient such as gender, age, body mass index (BMI), family history (FH), smoking habit, alcohol consumption, and pathological finding including the tumor size, tumor differentiation, circumferential involvement, tumor stage, node stage etc. Several studies considered the tumor size as an important factor for determining the stage of colon cancer [6][7][8][9], whereas some studies focused on evaluating the tumor size as a prognostic factor for the colorectal cancer prognosis [10,11]. It has also been found that the tumor size is not only an essential factor in determining the TNM stage of the colon cancer; it is also a significant predictor, which can be used for estimating the survival period of the patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy has also been used for palliative care in liver tumors (7)(8)(9). Modern radiotherapies, including stereotactic body radiation therapy (SBRT), intensity-modulated radiotherapy (IMRT), and particle therapies, have recently attracted increasing attention as therapeutic modalities for various malignancies and have dramatically increased the use of radiation therapy as a curative modality (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Abstract Surgical Resection Is the Standard Therapy Formentioning
confidence: 99%
“…In recent years, high tumor control rates post-SBRT have dramatically changed the role of radiotherapy from palliative care to radical intent. SBRT can provide 1-, and 2-year local control rates of 62-100%, and 45-100% for liver metastases, respectively, and is therefore a potential therapeutic candidate for the treatment of oligometastases (17,(21)(22)(23)(24)(25)(26).…”
Section: Sbrt For Metastatic Liver Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereotactic Body Radiation Therapy (SBRT) is an ablative technique characterized by the high dose delivered in one to five fractions with either the same or greater biologically effective dose as conventional radiotherapy . Studies have shown appreciable local control with the use of SBRT in primary and metastatic hepatic malignancies . SBRT has become the selected treatment of choice for patients who are not candidates for surgery due to tumor location .…”
Section: Introductionmentioning
confidence: 99%